1985
DOI: 10.1246/bcsj.58.1156
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion Complex Formation of γ-Cyclodextrin. One Host-Two Guest Complexation with Water-soluble Dyes in Ground State

Abstract: β-Cyclodextrin forms the 1:1 inclusion complex with Crystal Violet, Methylene Blue, Methyl Orange, or Congo Red in water. On the other hand, γ-cyclodextrin forms the 1:2 complex with Crystal Violet, Methylene Blue, or Methyl Orange, while the 1:1 complex is given with Congo Red. The one host-two guest complexations are shown on the bases of the changes of the electronic spectra, dependence of induced circular dichroisms on the concentrations of dyes, and the continuous variation methods with induced circular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…Some representative studies are cited. [94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110] Three-component CyD complexes are known. Several workers have investigated ternary complexes composed of a CyD, a guest, and an alcohol that seems to function as a "space-regulator" by optimizing the fit of the guest to the CyD cavity.…”
Section: Stoichiometric Ratiosmentioning
confidence: 99%
“…Some representative studies are cited. [94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110] Three-component CyD complexes are known. Several workers have investigated ternary complexes composed of a CyD, a guest, and an alcohol that seems to function as a "space-regulator" by optimizing the fit of the guest to the CyD cavity.…”
Section: Stoichiometric Ratiosmentioning
confidence: 99%
“…It is found that CR, like many azo dyes [29][30][31][32][33], has a strong tendency to aggregate. As shown by the UV-Vis spectral changes of CR in its small concentration (3.5×10 -5 M), CR molecules form face-to-face aggregates with zero or very little offset [34].…”
Section: Adsorption Of Cr On Cellulosementioning
confidence: 99%
“…found from the study using induced circular dichroism that β and γ CD form the 1:1 complexes with CR in water. 7,8) By using 1 H NMR spectrometry and 13 C NMR spectrometry, 9) it was confirmed that the benzene ring moiety of p nitrophenol or p nitrophenolate was included into the cavity of α CD, and it was reported that 1 Hs' chemical shifts of p nitrophenolate were observed with the addition of α CD and β CD. 10) NMR studies of aqueous solutions of γ CD and the azo dye CR show distinct, concentration independent 1 H NMR signals and that a very stable 1:1 pseudorotaxane is formed.…”
mentioning
confidence: 96%